Diseño de un plan estratégico para la mejora de la gestión y control de inventario de la Supertienda Olímpica 301 de la regional Montería (2022)
Inventory management is a very important process for the olympic company S.A. Take good control of it; It allows to have real, timely and reliable inventories, causing a continuous improvement in the supply processes, productivity and projected fulfillment of each POS. The company Olympic S.A. in each POS they handle a base of out of stock products that must always be displayed. This base of out-of-stock products are those products with the highest demand in businesses, which should be avoided reaching the out-of-stock status (Osorio, 2020) and at the same time contain timely inventories to avoid inaccuracies, negative balances and product freezing. In the following project, activities and mechanisms are proposed to be executed in warehouses so that when carrying out inventories and base reviews of out-of-stock products, they comply with all the protocols for display, return, breakdowns, avoid inaccuracies, reduce products into out-ofstock, both with the products that are ordered with direct suppliers such as those ordered by the manager and negative balances; thus fulfilling the proposed objective, based on the improvement of inventory management of the Olympic Superstore 301.